Peran Indonesia dalam Mewujudkan Stabilitas Keamanan Kawasan Regional Asean di Tengah Perebutan Pengaruh Negara-Negara Great Power - Jorry S. Koloay. Miknamara; Indra Indra (Jurnal Syntax Admiration, 2024)
Geopolitical developments in Southeast Asia have become the center of attention of major world powers, especially the United States and China. ASEAN, through the ADMM and ADMM-Plus forums, plays an important role in maintaining regional security stability. This study aims to analyze Indonesia's role in realizing security stability in the ASEAN region in the midst of great power competition. The research methods used are qualitative with in-depth interviews, case studies, and secondary data analysis from various sources, including policy reports and official government statements. The results of the study show that Indonesia plays a role as a diplomatic mediator, a reinforcer of regional cooperation, and a defender of ASEAN sovereignty. ADMM-Plus also faces challenges in expanding membership, which requires careful geopolitical considerations. In conclusion, Indonesia has a crucial role in maintaining regional stability through multilateral cooperation and conflict resolution efforts in ASEAN.